Study on the Use of Fertilizers and Manures in Agricultural Production - Planning Commission (Planning Commission, 1967)
Use of chemical fertilisers to boost up the crop yields has been accorded the topmost priority in the new strategy for agricultural production programmes during the Fourth Plan period. It is not that the importance of chemical fertilisers in the scheme of agricultural operations has suddenly been realised now. Over the entire period of fifteen years of planning, the importance of application of chemical fertilisers for the principal food and commercial crops has been fully recognised; not only that, concrete steps have been taken to augment the production and import of chemical fertilisers on the one hand and measures to distribute them throughout the country together with suitable facilities of credit, extension etc., on the other.
Programme Evaluation Organisation Planning Commission Government of India